2017
DOI: 10.2495/ws170201
|View full text |Cite
|
Sign up to set email alerts
|

Fast Simultaneous Electrochemical Detection of Tetracycline and Fluoxetine in Water

Abstract: The electrochemical methods-based protocol for simultaneous detection of tetracycline (TC) from antibiotics class and fluoxetine (FXT) from anti-depressive pharmaceuticals class, which belongs to emerging pollutants from water, was developed in this study using carbon nanofiber-epoxy composite electrode (CNF). The electrochemical behaviour of each pharmaceutical on CNF was considered the basis for simultaneous detection of both pharmaceuticals from water. TC electrooxidation on CNF occurred in two steps and, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Furthermore, Ardelean and team [ 90 ] showed that an electrode composed of carbon nanofiber-epoxy can be used to detect analytes in water samples simultaneously [ 90 ].…”
Section: Carbon–polymer Composite-based Modification Of Electrode Sur...mentioning
confidence: 99%
“…Furthermore, Ardelean and team [ 90 ] showed that an electrode composed of carbon nanofiber-epoxy can be used to detect analytes in water samples simultaneously [ 90 ].…”
Section: Carbon–polymer Composite-based Modification Of Electrode Sur...mentioning
confidence: 99%
“…The suggested method was successfully applied in the determination of PAR, CAF and ASA in pharmaceutical formulations with recovery ranging from 98 % to 108 % for PAR, 92 % to 104 % for CAF, and 92 % to 98 % for ASA. Tyszczuk‐Rotko and coauthors developed a DPV methodology for PAR and dopamine (DA) . DA is an important catecholamine neurotransmitter which plays a significant role in the proper functioning of the brain.…”
Section: Electroanalysis Of Pharmaceuticalsmentioning
confidence: 99%
“…Different antidepressant pharmaceuticals have an electroanalytical methodology developed. Fluoxetine (FXT), most usually known as Prozac®, was determined in tap water samples using SWV at BDD electrode . In the proposed electroanalytical method, FXT can be directly determined in a 0.1 mol L −1 Na 2 SO 4 .The electrochemical behavior and detection of FXT at BDD electrode were studied using CV, DPV, SWV and chronoamperometry (CA).…”
Section: Electroanalysis Of Pharmaceuticalsmentioning
confidence: 99%
“…Carbon-based materials have remarkable characteristics, such as: high surface area, high electrical conductivity, electron mobility at room temperature, flexibility and mechanical strength, making them very attractive in the field of sensor design. Of these carbonaceous materials, due to its electrical conductivity and very high surface area, graphene is ideal for electrochemical applications [20][21][22][23]. The boron diamond electrode (BDD) is recognized for its outstanding properties in very good results in electrochemical detection and electrochemical applications, such as: reproducibility, low background current, wide potential window, stability.…”
Section: Introductionmentioning
confidence: 99%